Pre- and neonatal exposure to lipopolysaccharide or the enteric metabolite, propionic acid, alters development and behavior in adolescent rats in a sexually dimorphic manner. - Kelly A Foley; Klaus-Peter Ossenkopp; Martin Kavaliers; Derrick F Macfabe (PLoS ONE, 2014)
Alterations in the composition of the gut microbiome and/or immune system function may have a role in the development of autism spectrum disorders (ASD). The current study examined the effects of prenatal and early life administration of lipopolysaccharide (LPS), a bacterial mimetic, and the short chain fatty acid, propionic acid (PPA), a metabolic fermentation product of enteric bacteria, on developmental milestones, locomotor activity, and anxiety-like behavior in adolescent male and female offspring. Pregnant Long-Evans rats were subcutaneously injected once a day with PPA (500 mg/kg) on gestation days G12-16, LPS (50 µg/kg) on G15-16, or vehicle control on G12-16 or G15-16. Male and female offspring were injected with PPA (500 mg/kg) or vehicle twice a day, every second day from postnatal days (P) 10-18. Physical milestones and reflexes were monitored in early life with prenatal PPA and LPS inducing delays in eye opening. Locomotor activity and anxiety were assessed in adolescence (P40-42) in the elevated plus maze (EPM) and open-field. Prenatal and postnatal treatments altered behavior in a sex-specific manner. Prenatal PPA decreased time spent in the centre of the open-field in males and females while prenatal and postnatal PPA increased anxiety behavior on the EPM in female rats. Prenatal LPS did not significantly influence those behaviors. Evidence for the double hit hypothesis was seen as females receiving a double hit of PPA (prenatal and postnatal) displayed increased repetitive behavior in the open-field. These results provide evidence for the hypothesis that by-products of enteric bacteria metabolism such as PPA may contribute to ASD, altering development and behavior in adolescent rats similar to that observed in ASD and other neurodevelopmental disorders.